Pituitary apoplexy during treatment of prolactinoma with cabergoline - Ghadirian, Hesam; Shirani, Mohamad; Ghazi-Mirsaeed, Shahab; Mohebi, Saleh; Alimohamadi, Maysam (Asian Journal of Neurosurgery, 2018)
Pituitary apoplexy is a rare clinical presentation caused by infarction of the pituitary gland or adenoma with or without hemorrhage. Although pituitary apoplexy is usually spontaneous, one of the predisposing factors is treatment with dopamine agonists, especially bromocriptine. The occurrence of apoplexy during cabergoline therapy is reported much less frequently. In this article, we report a 34-year-old man with macroprolactinomas who developed sudden visual deterioration due to pituitary apoplexy 1 year after initiation of cabergoline therapy. He was treated via endoscopic trans-sphenoidal surgery and his visual status recovered dramatically.
Keywords: Cabergoline; pituitary adenoma; pituitary apoplexy; prolactinoma